Digital Citizenship in EFL Education: Evaluating Learners’ Competencies and Teaching Practices in Pri-vate Universities in Bangladesh - Ahmed, Zohur (Journal of NELTA, 2025)
Digital citizenship has emerged as an important aspect of English language teaching (ELT) in the 21st century. This study investigates the digital citizenship skills of EFL students at private universities in Bangladesh as well as the strategies teachers use to help them develop their skills. In this study, a mixed-methods approach was followed. The quantitative data were collected from 123 under graduate EFL students from the department of English of three private universities in Dhaka, Bangladesh, through a Likert-scale survey evaluating their proficiency in information and data literacy, communication, content creation, digital safety, and problem-solving. Qualitative data were collected from 13 EFL teachers from four private universities in Bangladesh through an online qualitative survey using a Google Form, focusing on pedagogical strategies for promoting digital citizenship. The findings indicate that the students demonstrate moderate competency, with the highest scores in digital safety (3.73/5) and the lowest in digital content creation (3.37/5). Besides, no significant differences were found between male and female participants in total scores and in subscale scores in the digital competence scale. The findings also show that the teachers’ instructions include critical source evaluation of information and digital content, use of collaborative digital tools, practice of online responsibilities and digital etiquette, development and management of digital identity, ethical use of information and digital content, and protection of personal information and student well-being, all aligned with the Dig Comp 2.2: The Digital Competence Framework for Citizens. However, gaps remain in terms of content creation, improved collaboration tools, and methodological guidance on institutional digital literacy policies. This study emphasizes the need for structural integration of digital citizenship in EFL curricula, faculty training, and institutional support to better prepare students for academic and professional digital environments.